2010
DOI: 10.1002/asna.201011388
|View full text |Cite
|
Sign up to set email alerts
|

GREGOR solar telescope: Design and status

Abstract: The integration and verification phase of the GREGOR telescope reached an important milestone with the installation of the interim 1 m SolarLite primary mirror. This was the first time that the entire light path had seen sunlight. Since then extensive testing of the telescope and its subsystems has been carried out. The integration and verification phase will culminate with the delivery and installation of the final 1.5 m Zerodur primary mirror in the summer of 2010. Observatory level tests and science verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…M1 is also made light-weight (210 kg) by means of its honeycomb structure, and it is cooled from behind through more than 400 fan tubes. Again, tests have demonstrated that cooling works properly (Volkmer et al 2010).…”
Section: Construction Of Gregormentioning
confidence: 99%
See 1 more Smart Citation
“…M1 is also made light-weight (210 kg) by means of its honeycomb structure, and it is cooled from behind through more than 400 fan tubes. Again, tests have demonstrated that cooling works properly (Volkmer et al 2010).…”
Section: Construction Of Gregormentioning
confidence: 99%
“…Since it is located close to the entrance pupil the field stop has to be cooled to remove the heat from the enormous amount of sunlight, which would otherwise cause air motion. Tests were very positive and showed that the field stop reaches a temperature close to that of the ambient air (Volkmer et al 2010). Many of the other works were done by KIS, with support in the form of manpower from the other two institutes.…”
Section: Construction Of Gregormentioning
confidence: 99%
“…Where 1 ω is the angle between the incident slit and the optical axis, 1 ω′ is the angle between the exit slit and the optical axis. Finishing formula (5) and (6) are:…”
Section: Focus Length Of Collimatingmentioning
confidence: 99%
“…The reason of solar atmosphere has broken up is solar magnetic field, for example macula, granule, chromospheric eruption, CME and so on [1] [2] .As base on the prediction of solar activity, the goal that solar physicists have been relentless pursuit is getting violent solar activity clear picture understanding the outbreak of the mechanism. At present, we have obtained the general physical picture and mechanism of the outbreak of the sun, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The recently inaugurated 1.5-meter GREGOR solar telescope (Schmidt et al 2012a;Volkmer et al 2010) is a new solar facility with the potential for cutting-edge science at fundamental scales, i.e., the pressure scale-height, the photon mean-free path, and the intrinsic size of elemental magnetic structures. The key science topics of the GREGOR telescope are (see Schmidt et al 2012b): (1) the interaction between convection and magnetic fields in the photosphere, (2) the nature and dynamics of sunspots and pores and their temporal evolution, (3) the solar magnetism and its role in solar variability, and (4) the enigmatic heating mechanism of the chromosphere.…”
Section: Introductionmentioning
confidence: 99%